2018
DOI: 10.3390/ma11112094
|View full text |Cite
|
Sign up to set email alerts
|

Non-Isothermal Crystallization Kinetics of Short Glass Fiber Reinforced Poly (Ether Ether Ketone) Composites

Abstract: Due to its excellent chemical and temperature resistances, short glass fiber reinforced poly (ether ether ketone) composite (SGF/PEEK) is a promising material for application in automotive lightweight. Processing conditions, such as cooling rate, need to be well controlled to obtain the optimal crystallite morphology of PEEK composites. Thus, in this paper, the non-isothermal crystallization kinetics and melting behavior of SGF/PEEK were investigated by differential scanning calorimetry (DSC) at different cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…As expected, the T p of the crystallization exotherm decreases with an increasing cooling rate for each specimen. Similar behavior has been reported in PEEK and other polymer systems [46,47,48,49,50]. In addition, at each cooling rate, the addition of CNTs induces a higher T p .…”
Section: Resultssupporting
confidence: 83%
“…As expected, the T p of the crystallization exotherm decreases with an increasing cooling rate for each specimen. Similar behavior has been reported in PEEK and other polymer systems [46,47,48,49,50]. In addition, at each cooling rate, the addition of CNTs induces a higher T p .…”
Section: Resultssupporting
confidence: 83%
“…It can only be used to explain the primary crystallization phase when transformed into non-isothermal conditions. As both nucleation and crystallization process are affected by continues change in temperature, the effectiveness of the crystallization rate should be taken into account [19,26]. Jeziorny stated that the Avrami model could be utilized for non-isothermal crystallization process, which is based on the assumption that the cooling rate remains constant for a given sample [25].…”
Section: Non-isothermal Crystallization Kineticsmentioning
confidence: 99%
“…Sun at el. found that the crystallite size distribution evolved more uniform and the size of crystallites enlarged with the decreasing cooling rate, and the absolute value of the crystallization activation energy for fiber reinforced PEEK is lower than that of pure PEEK . Similar results also suggested that lower crystallization process promoted the formation of perfect crystal structures and prevented the deterioration of mechanical properties .…”
Section: Introductionmentioning
confidence: 73%